Hairy Fungus Beetles (Coleoptera, Mycetophagidae) of the Almaty Oblast (Sout-East Kazakhstan) - I. I. Temreshev (Acta Biologica Sibirica, 2019)
The hairy fungus beetles (Coleoptera: Mycetophagidae) in Almaty oblast of Kazakhstan is reviewed including diagnoses, illustrations, distributions, and natural history. Total 7 species and 3 genera were identified - Mycetophagus quadripustulatus, M. quadriguttatus, M. fulvicollis, M. multipunctatus, M. piceus, Litargus connexus and Typhaea stercorea. The data on the fauna of hairy fungus beetles of 3 protected areas of Almaty oblast are given. In the State national natural park "Ile-Alatau" all 3 genera and 7 species of Mycetophagidae found in Almaty oblast are noted. For the State national natural park Altyn-Emel, 3 genera and 5 species are indicated: M. quadripustulatus, M. quadriguttatus, M. piceus, Litargus connexus and T. stercorea. In the State national natural park "Zhongar-Alatau" 2 genera and 4 species were found: M. quadripustulatus, M. quadriguttatus, M. multipunctatus and T. stercorea. At present, the State national natural park “Ile-Alatau” is the richest in species diversity of hairy fungus beetles from the three specially protected natural territories in which research was conducted. Information about some species of fungi, on which hairy fungus beetles were marked, is presented for the first time. M. quadriguttatus has not previously been reported on Agaricus campestris, Russula betularum, Pleurotus dryinus, P. ostreatus, Сoprinellus domesticus, Lepista personata. M. quadripustulatus - not recorded on the fungi Bjerkandera fumosa, L. personata, Cortinarius purpurascens, P. dryinus and Agaricus bitorquis. M. piceus  - on B. fumosa, C. purpurascens and P. dryinus. M. multipunctatus  - on Trametes ochracea, L. personata, C. purpurascens, A. bitorquis, R. betularum, Lycoperdon pratense and P. dryinus. M. fulvicollis on T. ochracea, Cerioporus squamosus, Scleroderma citrinum  and P. ostreatus. Litargus connexus - on L. personata, C. purpurascens, T. ochracea and P. ostreatus. T. stercorea - on Antrodia serialis, C. purpurascens, T. ochracea, C. squamosus and Byssonectria terrestris.